Prevalence of ameloblastoma: A three-year retrospective study - Ramesh Tatapudi; Shaik Abdul Samad; Reddy Sudhakara Reddy; Naveen Kumar Boddu (Wolters Kluwer Medknow Publications, 2014)
Context: This study intends to assess the data on the prevalence and types of ameloblastoma reported in the Outpatient Department retrospectively, so that the distribution of ameloblastomas among this geographic area can be reported. Aims: To retrospectively analyze and evaluate the distribution and frequency of ameloblastoma cases based on the gender and histopathological types. Settings and Design: Retrospective study. Materials and Methods: Radiographs and biopsy records of all histologically diagnosed cases of ameloblastoma archived from January 2010 to December 2012 were retrieved from the Outpatient Department. Statistical Analysis: Descriptive statistics were performed to calculate the frequency and percentages of these variables. Age was stratified into various groups at 15-year intervals. The chi-square test for differences between two groups and the analysis of variance (ANOVA) test for differences among three or more groups were used. The level of statistical significance was set at P < 0.05. Results: From the data of ameloblastoma patients, about 30 cases were short-listed and their data was analyzed. It was found that the 15-30 year old age group had the highest percentage of occurrence (about 46.6%) among all cases. Frequently the posterior segment and vertical ramus of the mandible was involved. Radiographically, unilocular appearance was noted in 50% of the cases and unicystic ameloblastoma was the most frequently encountered histological subtype (49.9%). Conclusion: Studies on the incidence of ameloblastoma among the Indian population is rare. By performing a meta-analysis at the level of societies and geographic places, we can identify the demographic distribution of common odontogenic lesions like ameloblastoma among the various populations.